Investigating the Neolithic Presence in South-Central Oman: The DUQ-25A Rock Shelter - Maiorano, Maria Pia; Chlachula, Dominik; Danielisová, Alžběta; Garba, Roman (Études et Travaux, 2024)
Over the past decade, extensive surveys have been carried out in the wider area surrounding the city of Duqm (south-central Oman). During fieldwork in 2023, research on the Neolithic encampment in the Wādī Ṣayy area was conducted. Numerous locations surrounding this large wadi have yielded evidence of Neolithic occupation. The proximity to chert outcrops and the presence of elevated fluvial terrace systems overlooking the wadi floodplains likely played a pivotal role in attracting human habitation during that period. Among these sites, DUQ-25A stands out for its exceptional preservation and the abundance of flint scatters. The excavation at the site aimed to achieve multiple objectives: validating the site’s chronology, expanding our understanding of its spatial extent and occupational sequence and filling the gaps in our knowledge about Neolithic societies in south-central Oman. Our research aims to provide new perspectives for the study of the Early and Middle Holocene in Al-Wusṭā.